Quantitative determination of salvinorin A, a natural hallucinogen with abuse liability, in Internet-available Salvia divinorum and endemic species of Salvia in Taiwan - Lin, P.; Li, J.; Chen, S.; Chang, H.; McKetin, Rebecca (2014)
In recent years, recreational use of Salvia divinorum (Lamiaceae), a herbal drug that contains a hallucinogenic ingredient, salvinorin A, has become a new phenomenon among young drug users. In Taiwan, as in many other countries, dry leaves of S. divinorum and its related concentrated extract products are available via the Internet. Besides S. divinorum, there are many endemic Salvia species whose salvinorin A content is yet unknown. To understand the abuse liability of these products, the aim of this study was to assess the concentration of salvinorin A in endemic Salvia species and Internet-available salvinorin A-related products. Samples of S. divinorum were purchased via the Internet and samples of eight endemic species of Salvia were collected in Taiwan, including S. arisanensis Hayata, S. coccinea Juss. ex Murr, S. hayatana Makino ex Hayata, S. japonica Thumb. ex Murr, S. nipponica Miq. Var. formosana (Hayata) Kudo, S. scapiformis Hance, S. tashiroi Hayata. Icon. PI. Formosan, and S. keitaoensis Hayata. The content of salvinorin A was determined by high performance liquid chromatography (HPLC). Salvinorin A was extracted from the dry leaves of S. divinorum and endemic species of Salvia with methanol and analyzed on a C-18 column by isocratic elution with a mobile phase of acetonitrile-water. Salvinorin A was detected in S. divinorum, but not in the endemic Salvia species of Taiwan. Therefore, endemic species of Salvia in Taiwan may not possess hallucinogenic potential. However, the potential harm from S. divinorum available via the Internet should be thoroughly assessed in Taiwan, and control measures similar to those implemented in many other countries should be considered.